Rasch model of teacher readiness instrument for implementing science learning based on Balinese local wisdom - Ida Bagus Ari Arjaya; Anak Agung Inten Paraniti; Ni Putu Suarniti Noviantari (University of Muhammadiyah Malang, 2024)
Local culture has undergone significant shifts and alienations, leading to the neglect of societal values. This situation underscores the need for teachers to be well-prepared to incorporate local wisdom into science education, supporting Cultured-Based Learning. This study, conducted from January to June 2022, aimed to assess the relevance of items in a teacher readiness instrument for implementing local wisdom-based science learning in Bali. An ex post facto research design was employed to analyze the preparedness of 72 science teachers in Bali through a detailed questionnaire. The collected ordinal data were converted into an interval scale using the Method of Successive Interval (MSI) and analyzed using the Rasch Model with the Jamovi application to assess item relevance. The study's findings highlight the cognitive and emotional readiness of science teachers as being in the high category, while collegial support and instructional tools are in the low category. These results suggest that improving collegial features and instructional tools through lesson studies and workshops could enhance the integration of local wisdom into science education in Bali.